2022
DOI: 10.1002/fam.3084
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of the thermal and mechanical behaviour of steel and recycled aggregate concrete composite elements exposed to fire

Abstract: Using recycled aggregates in the production of concrete has been a viable alternative for sustainable development. Notwithstanding advanced information on this material at room temperature, its behavior when exposed to fire is still incipient. Thus, based on experimental analyses, the objective of this article is to evaluate the behavior of concrete produced with recycled aggregates for thermal insulation of steel elements, as well as to verify the physical and mechanical properties of these mixtures. For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…If RA are to be used for construction purposes, extensive research must be performed to determine their mechanical properties and durability. Therefore, many studies have investigated the effect of temperature on the residual mechanical properties of RA in the last decade 24–30 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If RA are to be used for construction purposes, extensive research must be performed to determine their mechanical properties and durability. Therefore, many studies have investigated the effect of temperature on the residual mechanical properties of RA in the last decade 24–30 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies have investigated the effect of temperature on the residual mechanical properties of RA in the last decade. [24][25][26][27][28][29][30] Zhao et al 31 tested the thermal properties of RA concrete at elevated temperatures. They concluded that the thermal conductivity of concrete decreases as the percentage of RA increases.…”
mentioning
confidence: 99%
“…The exposure of recycled aggregate concrete structures to high temperatures during fire scenarios degrades their mechanical properties [5][6]. A key fire safety design requirement according to European standard, EN 1992-1-2 [7] is that the load bearing capacity of concrete exposed to high temperature due to fire can be assumed.…”
Section: Introductionmentioning
confidence: 99%